Prediction of h -> gamma Z from h -> gamma gamma at the LHC for the IMDS3 model - Fortes, E. C. F. S. [UNESP]; Machado, A. C. B. [UNESP]; Montano, J. [UNESP]; Pleitez, V. [UNESP] (Iop Publishing Ltd, 2015)
We consider the decays h -> gamma gamma, gamma Z in the context of an extension of the Standard Model with two inert doublets and an additional S-3 symmetry. This model contributes to for these processes through new charged scalar-loops. Comparing our h -> gamma gamma with more precise available experimental data we can predict the behavior of h -> gamma Z since they depend on the same parameters. Our estimation for this channel is 1.05 times the standard model value, but it can be as high as 1.16 if we consider the +1 sigma uncertainty from the h -> gamma gamma data, and as low as 0.96 if we consider -1 sigma.
Keywords: particle physics; Higgs physics; radiative corrections